Assessing the effectiveness of a 4‐week online intervention on food literacy and fruit and vegetable consumption in Australian adults: The online MedDiet challenge. (21st July 2022) - Ng, Ashley H.; ElGhattis, Yasser; Biesiekierski, Jessica R.; Moschonis, George
Abstract: Australians fail to meet the daily recommended two and five serves of fruit and vegetable respectively, which increases mortality risk for non‐communicable diseases such as cardiovascular disease and type 2 diabetes. This study aimed to evaluate the effectiveness of an online intervention delivered through social media on food literacy and fruit and vegetable consumption in Australian adults. In a pre‐post single group experimental study, 29 participants completed the "online MedDiet challenge", a four‐week intervention delivered via Facebook. Infographics, recipes and informational videos aligned with food literacy concepts related to the Mediterranean Diet were shared with participants. Outcome measures included a validated food literacy questionnaire with two questions from the National Nutrition Survey to record fruit and vegetable consumption. The mean age of participants was 52 years (range: 25–67 years). Post intervention, food literacy improved between 21%–45% across each survey component. Participants also reported an increase in fruit and vegetable consumption by 0.6 and 1.3 serves per day ( p < 0.05) respectively. Social media holds potential for increasing fruit and vegetable consumption in adults through food literacy. Future research should focus on longer studies and larger cohorts to confirm that food literacy plays a key component to maintain sustainability of such interventions.